La «Gramàtica Valenciana» de Manuel Sanchis Guarner - Ferrando, Antoni (Caplletra. Revista Internacional de Filologia, 2015)
This article studies Sanchis Guarner's Gramàtica Valenciana, trying to assess its relevant contribution, referring not only to the author's ideology and established goal, but also to its historical context and to its Catalan as well as Valencian precedents, like Fabra on one side, and Fullana, Giner and Salvador, on the other.